Analisis Penggunaan Alat dan Teknik Pengendalian Mutu dalam Penerapan Sistem Manajemen Mutu pada Perusahaan Karet Bersertifikat ISO 9001:2008 - Nofriani Fajrah; Nilda Tri Putri (Jurnal Optimasi Sistem Industri, 2016)
The increasing competition in the global market and high consumer expectations for quality products, encourage companies to be able to produce quality products which meets international standards. One of the activities in improving quality that conform to product specifications is applying appropriate quality control system involving all aspects of the company that are integrated with the standard ISO 9001: 2008 as a guide. However, the rubber industry in West Sumatra still faces obstacles in the implementation of quality control techniques and tools of as experienced by ABC and XYZ. This study aimed to evaluate the application of quality control tools and techniques in the manufacturing company which is certified ISO 9001: 2008, ABC and XYZ. This research was conducted by calculating the value of DPMO (Defect Per Million Opportunities). Based on the results found that the two companies have different DPMO value. PT ABC obtained by 5,2σ sigma level from DPMO value of 94.33 for the types of defects whitespot and sigma level of 4,2σ of DPMO value of 3365.096 to defect type of metal, while the XYZ obtain sigma level of 5,3σ from DPMO value of 728.697 for the types of defects whitespot and sigma level of 4,8σ of DPMO value of 425.441 for the type of metal defects. From the analysis it can be concluded that the two companies have not been effective in applying the techniques and tools of quality control in accordance with the standards ISO 9001: 2008 in order to achieve continuous quality improvement. This is indicated by the key success factor of the implementation techniques and tools of quality control is not applied appropriately in achieving continuous quality improvement.